Designing an Organizational Learning Model for Innovation-Driven Business Environments - Yazdani, Ali; Saberi, Sina (Business, Marketing, and Finance Open, 2024)
Abstract: This study aims to design an organizational learning model tailored for innovation-driven business environments. This qualitative study was conducted using semi-structured interviews with 27 participants from various innovation-intensive industries. The interviews were analyzed through open, axial, and selective coding using NVivo software to identify key themes. Theoretical saturation was achieved, and the data were systematically categorized to develop an integrated model of organizational learning and innovation. Three core themes emerged from the data analysis: Learning Culture and Leadership, Innovation-Driven Practices, and Adaptation and Knowledge Sharing. The findings highlighted the critical role of leadership in fostering a culture that encourages continuous learning, experimentation, and innovation. Collaborative knowledge sharing and cross-functional learning were found to be essential for enhancing innovation performance. Organizations that embraced adaptability and were open to experimentation and risk-taking were more likely to succeed in innovation efforts. The study demonstrates that organizational learning is a key enabler of innovation in dynamic business environments. Leadership, knowledge sharing, and a culture of experimentation are critical factors for building an organization’s capacity for innovation. The proposed model offers a comprehensive framework for organizations to integrate learning processes into their innovation strategies. By fostering a learning-oriented culture and supporting collaboration and adaptability, organizations can enhance their ability to innovate and remain competitive in evolving markets.